“COMPARISON OF HAEMODYNAMIC EFFECTS OF UNILATERAL VERSUS BILATERAL SPINAL ANAESTHESIA IN INGUINAL HERNIORRHAPHY - Humaira Ahmad; Asif Sagheer; Samina Aslam (Journal of University Medical & Dental College, 2015)
ABSTRACTINTRODUCTION: Conventional spinal anesthesia has been used since 1899 and the most common side effect associated with it is hypotension. Unilateral spinal anesthesia has emerged over time as an alternative to the standard technique and offer beneﬁts in terms of minimal haemodynamic disturbances primarily by limiting the degree of sympathetic block. Patient satisfaction and home readiness is compareable to the bilateral spinal anesthesia.OBJECTIVES: To compare frequencies of hypotension with unilateral versus bilateral spinal anesthesia in patients undergoing inguinal herniorrhaphy. STUDY DESIGN: Randomized controlled trial SETTING: Department of Anesthesia and Intensive Care, Punjab Medical College and afﬁliated hospitals, Faisalabad. DURATION OF STUDY WITH DATES: Study was carried out over a period of six months from 2012-2011 to 19-06-2012. SUBJECTS AND METHODS: A total of 130 patients (65 patients in each group) were included in this study. In Group-A, patients received bilateral spinal anesthesia and in Group-B, patients received unilateral spinal anesthesia. RESULTS: Mean age of the patients was 33.5±2.5 and 34.3±3.1, in group-A and B, respectively. Mean height was 160.5±10.3 and 161.9±10.1 cm in group-A and B, respectively. In group-A mean weight was 69.8±09.4 kg and in group-B, 71.6±10.8 Kg. Hypotension developed in 16 patients (24.6%) of group-A and 5 patients (7.7%) of group-B. CONCLUSION: In this study, it was found that unilateral spinal anesthesia is associated with stable cardiovascular proﬁle and, therefore, is a valuable technique in high- risk patients